Study on the physicochemical and flavor characteristics of air frying and deep frying shrimp (crayfish) meat - Zhou, Mingzhu; Shi, Gangpeng; Deng, Yi; Wang, Chao; Qiao, Yu; Xiong, Guangquan; Wang, Lan; Wu, Wenjin; Shi, Liu; Ding, Anzi (Frontiers in Nutrition, 2022)
This study aimed to compare the changes in the quality characteristics of air-fried (AF) shrimps and deep-fried (DF) shrimps at different frying temperatures (160℃, 170℃, 180℃, 190℃). Results showed that compared with DF, the moisture and fat content of AF shrimps was lower, while the protein content was higher. At the same frying temperature, the fat content of the air-fried shrimps was 4.26-6.58 g/100g lower than that of the deep-fried shrimps. The smell of the AF and DF shrimps was significantly different from that of CK group. The electronic tongue results showed that AF have a roasted flavor. Gas chromatography-ion mobility spectrometry (GC-IMS) identified 48 compounds, and the content of volatile compounds detected in AF shrimps was lower than that in DF shrimps. Among of them, the highest level of volatile compounds content was found in the DF-190. E-2-pentenal, 2-heptenal (E) and methyl 2-methylbutanoate were identified only in DF shrimps. In addition, a total of 16 free amino acids (FAAs) were detected in shrimps. As judged by sensory evaluation, the AF shrimps at 170℃ were the most popular among consumers.